PENGARUH BUDAYA ORGANISASI, KEDISIPLINAN DAN MOTIVASI TERHADAP KINERJA PEGAWAI DI RUMAH SAKIT UMUM DAERAH (RSUD) dr. SOEDIRAN MANGUN SUMARSO KABUPATEN WONOGIRI - Iqfan Agfianto; Sri Hartono; Djumali Djumali (ITB AAS INDONESIA Surakarta, 2019)
This study has a purpose, namely 1) To know and measure partially the influence of organizational culture, discipline, and motivation on the performance of the RSUD dr. Soediran Mangun Sumarso, Wonogiri Regency. 2) To find out and measure the influence of organizational culture, discipline and motivation on the performance of RSUD dr. Soediran Mangun Sumarso Wonogiri. The population is all employees of RSUD dr. Soediran Mangun Sumarso, Wonogiri Regency, there are a total of 735 employees. The sample in the study was 74 respondents. Methods of collecting data using documentation and questionnaires or questionnaires. Data analysis using classic assumption test, multiple linear test, t test, f test, specified coefficient. Results and conclusions: 1) Partially, there was a significant effect of organizational culture, discipline, and motivation on the performance of RSUD dr. Soediran Mangun Sumarso. 2) There is an influence of organizational culture, discipline and motivation on the performance of RSUD dr. Soediran Mangun Sumarso. Keywords: organizational culture, discipline, motivation, performance